Speed estimation for induction motor using neural networks method - Goedtel, Alessandro; Nunes Da Silva, Ivan; Jose Amaral Serni, Paulo [UNESP]; Suetake, Marcelo; Franscisco Do Nascimento, Claudionor; Augusto Oliveira Da Silva, Sergio (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This work presents an alternative approach based on neural network method in order to estimate speed of induction motors, using the measurement of primary variables such as voltage and current. Induction motors are very common in many sectors of the industry and assume an important role in the national energy policy. The nowadays methodologies, which are used in diagnosis, condition monitoring and dimensioning of these motors, are based on measure of the speed variable. However, the direct measure of this variable compromises the system control and starting circuit of an electric machinery, reducing its robustness and increasing the implementation costs. Simulation results and experimental data are presented to validate the proposed approach. © 2003-2012 IEEE.
Keywords: artificial neural networks; speed estimator; Three-phase induction motors; Alternative approach; Experimental datum; Implementation cost; National energy policy; Neural network method; Speed estimation; Speed estimator; Three phase induction motor; Condition monitoring; Electric machinery; Energy policy; Machinery; Neural networks; Starting; Induction motors